Pool complexity and molecular diversity shaped topsoil organic matter accumulation following decadal forest restoration in a karst terrain. (March 2022) - Chen, Shuotong; Feng, Xiao; Lin, Qingmei; Liu, Chun; Cheng, Kun; Zhang, Xuhui; Bian, Rongjun; Liu, Xiaoyu; Wang, Yan; Drosos, Marios; Zheng, Jufeng; Li, Lianqing; et al.
Abstract: Fast accumulation of soil organic matter (SOM) following forest restoration shifted from cropland has been widely reported, but how the pools and molecular composition change across soil aggregate fractions remains unclear. In this study, undisturbed topsoil (0–10 cm) samples were collected across a decadal chronosequence of forest stands (RL10, RL20 and RL40) restored for 10, 20 and 40 years following maize cropland (CL) abandonment in a karst terrain of Guizhou, Southwest China. SOM changes were explored using the size and density fractionation of water-stable aggregates, 13 C isotopic signalling and biomarker analyses as well as 13 C solid-state NMR assays. Compared to that of CL, SOM content was increased by 24%, 79% and 181%, mass proportion of macroaggregates increased by 136%, 179% and 250%, and particulate organic matter (POM) increased by 13%, 108% and 382%, respectively at RL10, RL20 and RL40. With biomarker analyses, the relative abundances of plant-derived organics (lignin, cutin, suberin, wax and phytosterols), mostly protected in aggregates, increased, while those of microbe-derived OC, predominantly mineral bound, decreased in response to prolonged forest restoration. Calculated as per the Shannon diversity index (H'), changes in SOM pool complexity and molecular diversity were parallel to the SOM accumulation trend. The pool size ratio of POM to MAOM (mineral-associated organic matter) and the molecular abundance ratio of PL (plant-derived lipids) to ML (microbe-derived lipids) appeared to be indicative of SOM accumulation following forest restoration. With prolonged forest restoration, the topsoil OM shifted from microbial MAOM dominance to plant-derived POM dominance. Furthermore, the great topsoil OM enhancement in restored forest stands was shaped by pool complexity and molecular diversity changes with the complex interactions among plant-microbial-mineral assemblages in the karst topsoil. Both the pool complexity and molecular diversity of SOM should be considered in addressing carbon sequestration with forest restoration concerning the functioning of soil ecosystems and services under global change pressures. Graphical abstract: Image 1 Highlights: SOM pool and composition analysed in a karst soil chronosequence of forest restoration from cropland. SOM storage and soil aggregation greatly enhanced following 40 years forest restoration. SOM shifted from microbial MAOM dominated to plant-derived POM dominated with prolonged restoration. Pool ratio of POM to MAOM and abundance ratio of plant- to microbe- derived lipids depict SOM accumulation with restoration. Changes in SOM pool complexity and molecular diversity were parallel to SOM accumulation trend.